Prevalence of Varroa spp. correlated to the productive and temperamental factor in the apiary of the Fundo Tartar Pecuario – Universidad Nacional de Cajamarca, Peru - Murga-Moreno, César Andreé (2021)
Varroasis is a disease caused by arachnids of the genus Varroa, an obligatory parasite of bees and the cause of high mortality. The present study aimed to report the prevalence of Varroa spp in the apiary of the Fundo Tartar Pecuario of the National University of Cajamarca, Peru and the possible resistance factors associated with the production and temperament of the hives and nuclei. The sampling was carried out in December 2019. The average prevalence of Varroa spp in the four nuclei sampled was 1.62 ± 0.61% and in the three hives it was 1.11 ± 0.5%, being 1.39 ± 0.41% for the apiary. All the nuclei and hives were classified with good production (1 to 2 floors) and in terms of temperament: 1 calm nucleus, 1 aggressive and 2 very aggressive, while the three hives were very aggressive. It is concluded that the quality of being a nucleus or hive does not influence the production or temperament of the bees. Furthermore, temperament or production are not related to the presence of Varroa spp in the apiary.